2007
DOI: 10.1038/sj.onc.1210685
|View full text |Cite
|
Sign up to set email alerts
|

Antizyme, a mediator of ubiquitin-independent proteasomal degradation and its inhibitor localize to centrosomes and modulate centriole amplification

Abstract: The potential tumor suppressor antizyme and its endogenous inhibitor (antizyme inhibitor, AZI) have been implicated in the ubiquitin-independent proteasomal degradation of proteins involved in cell proliferation as well as in the regulation of polyamine levels. We show here that both antizyme and AZI concentrate at centrosomes and that antizyme preferentially associates with the maternal centriole. Interestingly, alterations in the levels of these proteins have opposing effects on centrosomes. Depletion of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
36
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 31 publications
8
36
1
Order By: Relevance
“…AZ was also reported as a regulator of Smad1 when it functions as a transcriptional regulator of various BMP-responsive genes. Recently, Mangold et al reported on the function of antizyme as a centrosomal homeostasis (33). Although, in our study, we showed another aspect of antizyme, in that antizyme regulates the expression of ICDH and catalase, which is followed by a change of the ROS scavenging activity, we did not unveil whether the interacting target of antizyme for this physiological phenomenon is ODC or other factors.…”
Section: Discussioncontrasting
confidence: 42%
“…AZ was also reported as a regulator of Smad1 when it functions as a transcriptional regulator of various BMP-responsive genes. Recently, Mangold et al reported on the function of antizyme as a centrosomal homeostasis (33). Although, in our study, we showed another aspect of antizyme, in that antizyme regulates the expression of ICDH and catalase, which is followed by a change of the ROS scavenging activity, we did not unveil whether the interacting target of antizyme for this physiological phenomenon is ODC or other factors.…”
Section: Discussioncontrasting
confidence: 42%
“…In addition, the relative contribution of the antizyme-mediated perturbation of cyclin D1 and aurora-A on the process of cellular proliferation remains unclear. It was also recently demonstrated that antizyme-1 and its inhibitory protein, antizyme inhibitor, localize to centrosomes, and that alteration of their relative levels affect centriole amplification, thus contributing to oncogenesis [81]. Ectopic expression of antizyme was also implicated in activation of genes involved in DNA repair resulting in increased radio-resistance of these cells [82].…”
Section: Effect Of Antizyme On Other Proteinsmentioning
confidence: 97%
“…It is also worth noting that centrosomal Mps1 is degraded by an ubiquitin-independent proteasomal degradation mechanism mediated by Antizyme, a highly conserved protein that localizes to the centrosome, binds non-ubiquitinated substrates and targets them to the proteasome for degradation. 50,51 Loss of Antizyme-mediated Mps1 degradation results in centrosome amplification and contributes to aberrant MTOC activity and subsequent aneuploidy in human melanomas. 52 Antizyme regulation of centrosome duplication via Mps1 degradation suggests diverse modes of proteasome-mediated degradation, including ubiquitin-independent proteolysis, are utilized by centrosome-associated proteasomes.…”
Section: Centrosome Function Depends On the Proteasomementioning
confidence: 99%